Evidence-based skills in criminal justice : international research on supporting rehabilitation and desistance - Ugwudike, Pamela, 1969-; Raynor, Peter; Annison, Jill (Bristol, UK : Policy Press, 2018)
This book is the first to bring together international research on evidence-based skills and practices in probation and youth justice in the public, private and voluntary sectors. Wide-ranging in scope, it also covers effective approaches to working with ethnic minority service users, women and young people.
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: Criminals -- Rehabilitation; Evidence-based social work